A qualitative analysis of body representation in Netflix audio descriptions - Ahmad S. Haider; Sausan Abu Tair; Mohammed Dagamseh (Training, Language and Culture)
With the rise of streaming platforms like Netflix, viewers now have greater access to language and accessibility features. Audio description (AD) translates visual information into spoken language, enabling access for viewers with visual impairments. To match the experience of sighted audiences, AD must convey all visual cues, including physical appearances. Despite its importance, this area – where accessibility and inclusivity intersect – remains understudied. This paper investigates how Netflix’s AD represents different body types, physiques, and visible disabilities among able-bodied and disabled individuals. Using a qualitative descriptive approach, the study analyses AD in two series, one film, and one documentary to assess clarity, accuracy, consistency, and implications of these descriptions. Findings reveal inconsistencies in describing body shape and size, with such references being rare and often contingent on plot relevance. Descriptions typically appear in contexts tied to body image or physical performance, especially relating to athleticism and (dis)ability. In cases involving disability, AD often describes mobility aids rather than the individuals themselves – an approach that avoids potentially offensive terms but risks reinforcing the taboo around discussing disability. The study suggests that these inconsistencies stem from both linguistic limitations and a reliance on perceived relevance. It concludes that prevailing discourse and stigma around describing human bodies complicate AD practices. Further research is needed to refine AD guidelines, ensuring they reflect the perspectives of both those being described and those who rely on AD.